Effect of silica aerogel on the thermal conductivity of cement paste for the construction of concrete buildings in sustainable cities - Khamidi, M. Faris (WIT Press, 2014)
The objective of this paper is to evaluate the effect of silica aerogel on the thermal conductivity of cement paste for the construction of concrete buildings in sustainable cities. Samples consisting of Ordinary Portland Cement (OPC), free water and different volumes of silica aerogel were prepared and cured for three (3), seven (7) and 28 days. Compressive strength tests were performed on samples at three (3), seven (7) and 28 days of curing. Porosity and thermal conductivity tests were conducted on samples at 28 days of curing. The lowest thermal conductivity measured was 0.076 W/mK, which was achieved by sample mix with 20 ml of silica aerogel (M20), which represents a 93.58% reduction in thermal conductivity relative to the control mix. The highest permeable porosity measured for cement paste incorporated with silica aerogel was 25.6%, which was also obtained by sample M20. However, the highest compressive strength measured was 54.33 MPa, which was obtained by sample mix with 10 ml of silica aerogel (M10) at 28 days of curing. The addition of silica aerogel as filler in cement paste can reduce the thermal conductivity of cement paste at the expense of reduced compressive strength and increased permeable porosity.